THE ECONOMIC CONTRADICTIONS OF THE FOOD INDUSTRY IN THE WTO'S FRAMES - Зобенко, Н. Г. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2012)
The economic problems and contradictions of the Ukrains trade relationship with other countries in provision sphere were considered in the World Trade Organizations frames in the article.